Proceedings of the 25th Conference on Formal Methods in Computer-Aided Design – FMCAD 2025 (Conference Series: Formal Methods in Computer-Aided Design, 2025)
The Conference on Formal Methods in Computer-Aided Design (FMCAD) is an annual conference on the theory and applications of formal methods in hardware and system verification. FMCAD provides a leading forum to researchers in academia and industry for presenting and discussing groundbreaking methods, technologies, theoretical results, and tools for reasoning formally about computing systems. FMCAD covers formal aspects of computer-aided system design including verification, specification, synthesis, and testing.